Comparison of the Axes and Positions of the Uterus and Vagina Between Women With and Without Pelvic Floor Organ Prolapse - Li, Song; Wen, Xuewei; Gao, Zhenhua; Ke, Kunbin; Yang, Jing; Wang, Haifeng; Mo, Yin; Zeng, Yizhen; Li, Yuan; Tian, Daoming; Shen, Jihong (Frontiers in Surgery, 2022)
Abstract Purpose: To analyze the role of the axial position of the uterus and vagina in pelvic floor support, provide theoretical support for the evaluation of pelvic floor function, and improve the understanding of pelvic floor pathogenesis. Methods: Magnetic resonance imaging (MRI) data of 81 women with prolapse (prolapse group) and 57 women without prolapse (non-prolapse group) were collected. The length and angles of the upper, middle, and lower axes of the vagina, uterine body, and cervix were compared on MRI. These angles and the pelvic inclination correction system (PICS) line were compared. The coordinate parameters of the anatomical points of the uterus and vagina were measured, and their positions were analyzed. Results: In the prolapse group, the uterine body-cervical and cervical-upper vaginal angles were smaller (p < 0.05), uterine body and cervical-PICS line angles were smaller (p < 0.05), middle-lower vaginal angle was larger (p < 0.05), upper and middle vaginal-PICS line angles were larger (p < 0.05), lower vaginal-PICS line angle was smaller (p < 0.05), cervical length was longer (p < 0.05), and middle and lower vagina lengths were shorter (p < 0.05) than those in the non-prolapse group. The coordinate system revealed that the uterine and vaginal axes were shifted backward and downward. Conclusion: The uterus in the prolapse group showed retroversion and retroflexion. The vagina was shortened, turned forward, and straightened. The uterus and vagina moved backward and downward. Changes in the axial position of the uterus and vagina are important mechanisms of pelvic floor organ prolapse.